Pengaruh Suasana Toko Terhadap Pembelian Impulsif (Kajian Empiris Pada Gerai Miniso di Kota Bandung) - Maya Setiawardani (Jurnal Riset Bisnis dan Investasi, 2019)
Store atmosphere is one of the important strategies in the field of marketing, especially for retail outlets because the atmosphere of the store can affect the emotions and feelings of customers to take action such as impulsive purchases. In addition, some Indonesian consumers have an unplanned character in purchasing (impulsive buying) caused by emotional and spontaneous attraction to a particular atmosphere, and often no longer involve rationality in the decision making process. This study aims to determine the effect of store atmosphere on impulsive buying made by customers from Miniso retail outlets in the city of Bandung. Store atmosphere is a store arrangement that is carried out in such a way as to create an overall emotional effect on customers through the five senses so that it can attract customers to come and finally make purchasing decisions.